Authenticity, Interactivity, and Collaboration in Virtual Reality Games: Best Practices and Lessons Learned - Wang, Annie; Thompson, Meredith; Uz-Bilgin, Cigdem; Klopfer, Eric (Frontiers in Virtual Reality, 2021)
Virtual reality has become an increasingly important topic in the field of education research, going from a tool of interest to a tool of practice. Although research on VR has progressed greatly in the last 10 years, additional scholarship is necessary to document long-term studies of VR projects. In this paper, we document and summarize the studies associated with our four-year design project, Collaborative Learning Environments in Virtual Reality (CLEVR). Our goal is to share the lessons we gleaned from the design and development of the game so that others may learn from our experiences as they are designing, developing, and testing VR for learning. We translate “lessons learned” from our user studies into “best practices” when developing authentic, interactive, and collaborative experiences in VR. We learned that authentic representations can enhance learning in virtual environments but come at a cost of increased time and resources in development. Interactive experiences can motivate learning and enable users to understand spatial relationships in ways that two dimensional representations cannot. Collaboration in VR can be used to alleviate some of the cognitive load inherent in VR environments, and VR can serve as a context for collaborative problem solving with the appropriate distribution of roles and resources. The paper concludes with a summation of best practices intended to inform future VR designers and researchers.